Identifikasi Postur Kerja Karyawan Penghalusan Divisi IP PT Pindad dengan Pendekatan Ergonomi - Anggara Yuda, Wisnu; Maharani Suyono, Annisa (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Transportation Infrastructure Division of PT. Pindad is a strategic business unit that focuses on the production of railway infrastructure and marine equipment for local and export markets. One of its mainstay products is gongsol, which is an additional rail on sharp bends that functions to reduce wheel slippage and rail wear. The Fabrication, Construction, and Mechanical Department produces gongsol through a mechanical fabrication and assembly process. However, there was a discrepancy between the production time standards on the routing sheet and actual conditions in the field, especially in the afbrament process. This process is carried out by five employees in a squatting position for 8 hours per day. The purpose of this study was to identify complaints of pain using the NBM Method, identify work positions based on the level of danger using the REBA Method and make recommendations for drafting improvements. This study was conducted by interviewing & direct observation of employees in the afbrament process and Indonesian anthropometric standard data. The results of the analysis showed a final score of Rapid Entire Body Assessment of 9, which indicates the need for immediate improvement. Therefore, the design of an ergonomic work desk is recommended to reduce the risk of musculoskeletal disorders and increase work comfort. Keywords: Musculoskeletal Disorder, NBM, REBA, Work Posture, Work System Improvement